Evidence for synergistic control of glutamate biosynthesis by glutamate dehydrogenases and glutamate in Bacillus subtilis. (27th March 2015) - Stannek, Lorena; Thiele, Martin J.; Ischebeck, Till; Gunka, Katrin; Hammer, Elke; Völker, Uwe; Commichau, Fabian M.
Summary In the Gram‐positive bacterium, Bacillus subtilis glutamate is synthesized by the glutamine synthetase and the glutamate synthase (GOGAT). During growth with carbon sources that exert carbon catabolite repression, the rocG glutamate dehydrogenase (GDH) gene is repressed and the transcription factor GltC activates the expression of the GOGAT encoding gltAB genes. In the presence of amino acids of the glutamate family, the GDH RocG is synthesized and the enzyme prevents GltC from binding to DNA. The dual control of glutamate biosynthesis allows the efficient utilization of the available nutrients. Here we provide genetic and biochemical evidence that, like RocG, also the paralogous GDH GudB can inhibit the transcription factor GltC, thereby controlling glutamate biosynthesis. Contradictory previous observations show that high level of GDH activity does not result in permanent inhibition of GltC. By controlling the intracellular levels of glutamate through feeding with exogenous arginine, we observed that the GDH‐dependent control of GltC and thus expression of the gltAB genes inversely correlates with the glutamate pool. These results suggest that the B. subtilis GDHs RocG and GudB in fact act as glutamate sensors. In conclusion, the GDH‐mediated control of glutamate biosynthesis seems to depend on the intracellular glutamate concentration.